Digital Illicit Trade and Sharia Compliance: Assessing Illegal Cigarette Transactions on Facebook in Indonesia - Cep Hamdi; Cucu Susilawati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
Illegal cigarettes are cigarettes that have not paid excise duty and therefore lack excise stamps. Illegal cigarettes clearly violate excise laws and regulations. However, this practice remains widespread, particularly through Facebook. Therefore, the purpose of this study is to analyze the legality of illegal cigarette sales on Facebook from the perspective of Islamic economic law. The legal requirements for sales and purchases may differ between positive law and Islamic economic law. This study uses an empirical legal approach with a descriptive method. The type of data in this study is qualitative data. The data sources used are primary and secondary data. Moreover, data collection techniques are carried out through interviews, documentation, and literature studies. The results of this study are that illegal cigarette trading on the Facebook application is carried out through a group containing sellers and buyers. The process of offering goods is carried out in the group. At the same time, payments can be made by transfer or COD, according to the parties' agreement. Second, the community has not complied with Law Number 39 of 2007. Therefore, illegal cigarette trading is widely carried out directly and online. Third, according to Sharia Economic Law, illegal cigarette trading fulfils the pillars of buying and selling in Islam. However, illegal cigarette trading does not meet the requirements for valid trading in Islam, including the non-halal nature of the goods being traded and the cigarettes obtained by the seller are the result of smuggling. Therefore, illegal cigarette trading is included in invalid trading and is not by Sharia principles because it contains crimes related to property. In conclusion, illegal cigarette trading is prohibited and is not by Sharia economic law and violates Law Number 39 of 2007 concerning Excise.